Factors influencing fumonisin B1 contamination in maize: insights from two production regions in Costa Rica - Sánchez Zúñiga, Katherine (2024)
Maize (Zea mays L.) is an important cereal crop worldwide. Contaminated maize kernels pose a significant mycotoxin exposure risk for humans in Latin America. Fumonisins, the most prevalent mycotoxin in maize, typically occur during pre-harvest conditions leading to significant economic losses. Various factors, including weather conditions, may influence this contamination. This study aimed to determine the association between fumonisin B1 (FB1) contamination, prevalence of Fusarium verticillioides, weather conditions and kernel quality in the two primary maize production areas in Costa Rica (Brunca and Chorotega). All maize samples (100%) showed FB1 contamination, with higher concentrations in samples from Brunca region, consistent with the presence of F. verticilliodes. Weather conditions appeared to play an important role in this contamination, since Brunca region had the highest mean temperature and relative humidity after maize silking (R1) and the total monthly rainfall in this region was significantly higher during the last two months of maize cultivation (grain-filling and physiological maturity stages R3 to R6). Interestingly, this study found a negative correlation between grain damage and kernel contamination with FB1 and F. verticillioides. The concentration of mineral nutrients in kernels from both regions was largely similar. Most nutrients in kernels exhibited a negative correlation with FB1, particularly nitrogen. Zinc and phosphorus were the only nutrients in kernels showing a positive correlation with FB1 in samples from the Brunca region. The results highlight elevated levels of FB1 contamination in maize and contribute to a better understanding of pre-harvest factors influencing FB1 contamination in tropical conditions.